CXCR3 chemokine receptor contributes to specific CD8+ T cell activation by pDC during infection with intracellular pathogens - Ferreira, Camila Pontes (2020)
Universidade Federal de São Paulo. Departamento de Microbiologia, Imunologia e Parasitologia. São Paulo, SP, Brasil.